Nebulised Gadolinium-Based Nanoparticles for a Multimodal Approach: Quantitative and Qualitative Lung Distribution Using Magnetic Resonance and Scintigraphy Imaging in Isolated Ventilated Porcine Lungs - Montigaud Y (Dove Medical Press, 2020)
Yoann Montigaud,1 Jérémie Pourchez,1 Lara Leclerc,1 Olivier Tillement,2 Anthony Clotagatide,3,4 Clémence Bal,5 Noël Pinaud,5 Nobuyasu Ichinose,6 Bei Zhang,7 Sophie Perinel,3,4 François Lux,2,8 Yannick Crémillieux,5 Nathalie Prevot3,4 1Mines Saint-Etienne, Univ Lyon, Univ Jean Monnet, INSERM, U 1059 Sainbiose, Centre CIS, Saint-Etienne, France; 2Institut Lumière Matière, Université de Lyon, Villeurbanne, France; 3INSERM U 1059 Sainbiose, Université Jean Monnet, Saint-Etienne, France; 4CHU Saint-Etienne, Saint-Etienne, France; 5IBIO, Bordeaux, France; 6Canon Medical Systems Corporation, Otawara, Japan; 7Canon Medical Systems Europe, Zoetermeer, Netherlands; 8Institut Universitaire de France (IUF), Paris, FranceCorrespondence: Jérémie PourchezMines Saint-Etienne, 158 Cours Fauriel, CS 62362, Saint-Etienne, Cedex 2 42023, FranceTel +33 4 77 42 01 80Email pourchez@emse.frPurpose: This study aims at determining lung distribution of gadolinium-based polysiloxane nanoparticles, AGuIX® (small rigid platform – SRP), as a potential theranostic approach by the pulmonary route.Methods: First, the aerodynamic size distribution and the aerosol output rate were thoroughly characterized. Then, a multimodal approach using magnetic resonance (MR) and gamma-camera (GC) imaging allows to assess the deposition of the aerosolised nanoparticles in the respiratory tract using isolated ventilated porcine lungs.Results: The SRP has proven to be radiolabelled by radioisotope with a good yield. Crude SRP or radiolabelled ones showed the same aerodynamic size distribution and output as a conventional molecular tracer, as sodium fluoride. With MR and GC imaging approaches, the nebulised dose represented about 50% of the initial dose of nanoparticles placed in the nebuliser. Results expressed as proportions of the deposited aerosol showed approximately a regional aerosol deposition of 50% of the deposited dose in the lungs and 50% in the upper airways. Each technique assessed a homogeneous pattern of deposited nanoparticles in Lungs. MR observed a strong signal enhancement with the SRP, similar to the one obtained with a commonly used MRI contrast agent, gadoterate meglumine.Conclusion: As a known theranostic approach by intravenous administration, SRP appeared to be easily aerosolised with a conventional nebuliser. The present work proves that pulmonary administration of SRP is feasible in a human-like model and allows multimodal imaging with MR and GC imaging. This work presents the proof of concept of SRP nebulisation and aims to generate preclinical data for the potential clinical transfer of SRP for pulmonary delivery.Keywords: aerosol, pulmonary delivery, ex vivo model, MRI, SPECT/CT, theranostic